The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1742-6596/1569/2/022095
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Economic Order Quantity Model: A Model Consider Transportation, Warehouse, Emission Carbon Costs, and Capacity Limits

Abstract: Recently, the problem of minimizing emission carbon in the industry has become a focus of much research. One of the efforts that were successfully carried out was managing the sustainable economics order quantity (SEOQ). However, several SEOQ had assumption such as (1) Transportation and warehouse costs are ignored, (2) Transportation emissions are avoided, and (3) warehouse Capacity Limit are ignored. In this paper, we developed the SEOQ model with warehouse costs and capacity limits. There are two proposed S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…is decision impacts the low frequency of delivery. However, the inventory costs incurred are high, causing high operating costs for the company [14][15][16]. In addition to transportation problems, the problem of decreasing quality is an important problem in inventory [17].…”
Section: Introductionmentioning
confidence: 99%
“…is decision impacts the low frequency of delivery. However, the inventory costs incurred are high, causing high operating costs for the company [14][15][16]. In addition to transportation problems, the problem of decreasing quality is an important problem in inventory [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the allocation order, fuel transportation cost received less attention in the GSSOA issue. The transportation sector contributes the most significant carbon emissions in the world [26]- [28]. However, the goal allocation order does not only minimize fuel transportation costs.…”
Section: Introductionmentioning
confidence: 99%
“…Bouchery, et al [26] suggested a multi-objective model of sustainable transportation and order quantity. The model involving Transportation, Warehouse, Emission Carbon Costs, and Capacity Limits was proposed by Utama, et al [27].…”
Section: Introductionmentioning
confidence: 99%
“…This study tried to develop a sustainable EOQ model with Multi Container Transportation Problems. This research model was developed from research conducted by Utama, et al [27]. In the previous model, they did not consider the number of containers transported.…”
Section: Introductionmentioning
confidence: 99%